Evaluation of asphalt–aggregate interaction based on the rheological properties. Issue Volume 19:Issued 7(2018) (3rd July 2018) - Zhang, Jiupeng; Fan, Zepeng; Hu, Dongliang; Hu, Zhuang; Pei, Jianzhong; Kong, Weichuan
Abstract: The silicon dioxide (SiO2 ) and calcium oxide (CaO) analytical reagents are selected to prepare asphalt mastics and the effects of aggregate chemical composition on asphalt–aggregate interactions (AAI) are evaluated based on the complex modulus and phase angle. It is found that the oxide analytical reagents significantly affect the rheological properties such as complex shear modulus and phase angle, and the effects of CaO are greater than SiO2 due to the stronger interaction between asphalt binder and CaO analytical reagents. Both the modulus stiffening ratio and the phase angle-based K. Ziegel - B coefficient could be used to evaluate the AAI, and the latter is the better index. Results show that the indexes increase with the test temperature, but decrease with the loading frequency, and tend to be constant. The higher adhesive strength between asphalt binder and limestone than basalt is likely attributed to the higher content of CaO in limestone aggregate and the stronger asphalt–CaO interaction.